Women playing volleyball against EAC - Weissman, Mike (Tufts Archival Research Center, 2014)
This date is approximate. 5 x 7 in., photographic print. Back of print reads: "10/16 vs EAC; by Mike Weissman; pg 7; 58%; Bottom left"